Greece : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper explores the links between wage policies, non-wage cost developments, and competitiveness. A series of program-era policies helped to partially reverse this trend, including labor market policies that cushioned the effect of the crisis on employment and brought unit labor costs broadly in line with trading partners. However, the resulting more competitive wage structure only partly translated into price adjustments due to product market rigidities (with firms retaining some profit margin) and rising non-wage cost factors (e.g., taxes and financing costs). This incomplete internal devaluation and subsequent low productivity gains reinforce the view that Greece has further to go to address its external imbalances. However, labor policy reversals following program exit in August 2018 threaten this objective. The paper shows that Greece must preserve its labor cost competitiveness while increasing efforts to facilitate price adjustment in product markets and reduce non-wage costs.